Morphology and distribution of three araphid diatoms (Fragilariophyceae, Bacillariophyta) from marine coastal waters of Argentina - Sunesen, Inés (2015)
This study deals with the morphology, taxonomy and distribution of three species of araphid marine pennate diatoms belonging to the Class Fragilariophyceae, Subclass Fragilariophycidae. Material was collected in marine coastal waters from the provinces of Buenos Aires and Río Negro (Argentina) and analyzed using light and scanning electron microscopy. Pravifusus inane (Giffen) Garcia and Pteroncola inane (Giffen) Round, were found in the water column, and Pseudohimantidium pacifcum Hustedt & Krasske was recorded as epizoic on planktonic copepods. The three genera are cited for the frst time in Argentina, and Pteroncola inane for frst time in the South Atlantic Ocean. The distribution of Pravifusus inane and Pseudohimantidium pacifcum is extended southward in the Southwest Atlantic Ocean, and the distribution of Pteroncola inane is extended to the Southwest Atlantic Ocean. The order Protoraphidales Round was validated by providing a taxonomic characterization, as well as indicating the generitype.